2021
DOI: 10.1017/jfm.2021.110
|View full text |Cite
|
Sign up to set email alerts
|

Channel flow with large longitudinal ribs

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 36 publications
8
40
0
Order By: Relevance
“…2b,c. The profiles confirm that the HMP and downwash region is located in between the ridges while the LMP and upwash is observed above the ridges which is consistent with observations in the literature (Vanderwel and Ganapathisubramani, 2015;Medjnoun et al, 2018;Castro et al, 2021). The ongoing progress of this work includes: stereo-PIV measurements in the cross-plane, frequency analysis, and quantification of inner-outer interactions in this flow scenario.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2b,c. The profiles confirm that the HMP and downwash region is located in between the ridges while the LMP and upwash is observed above the ridges which is consistent with observations in the literature (Vanderwel and Ganapathisubramani, 2015;Medjnoun et al, 2018;Castro et al, 2021). The ongoing progress of this work includes: stereo-PIV measurements in the cross-plane, frequency analysis, and quantification of inner-outer interactions in this flow scenario.…”
Section: Resultssupporting
confidence: 89%
“…In a particular scenario, when the surface heterogeneity is predominantly in the spanwise direction of the flow, this roughness heterogeneity can generate secondary flow in cross flow plane which is very different from smooth-wall or homogeneous rough-wall boundary layers. A number of experimental (Barros and Christensen, 2014;Vanderwel and Ganapathisubramani, 2015;Zampiron et al, 2020) and numerical (Anderson et al, 2015;Hwang and Lee, 2018;Castro et al, 2021) studies have shown features associated with the secondary flow including: streamwise oriented alternating lowand high-momentum pathways (LMP, HMP); downwash and upwash flow at HMP and LMP, respectively; counter-rotating streamwise vortices formed across an LMP and HMP. The secondary flow mechanism is explained based on Prandtl's secondary flow of the second kind according to Anderson et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…( 2)) at every time instant of the simulation. This IBM implementation was validated for rough surfaces by Forooghi et al (2018) and has successfully been used in previous works on secondary motions generated through longitudinal ribs (Stroh et al 2019;Castro et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, novel modelling concepts for spanwise irregular rough surfaces have to be developed as outlined by Chung et al (2021). It was recently demonstrated by Castro et al (2021) that the spanwise averaged flow field above streamwise aligned ribs can be described with a modified log-law taking into account the increase of wetted surface area. It might thus be possible to predict the global effect of ridge-type roughness onto the spanwise averaged flow field through a prescription of a velocity profile that is tuned to include the Reynolds number dependency of the generated friction drag.…”
Section: Reynolds Number Dependency Of the Friction Coefficientmentioning
confidence: 99%
“…As noted in [81], the term "roughness" is used sometimes by different research groups in different meanings. Two different types of the wall structuring can be meant under this term, namely, small-scale (about 10% of the boundary layer thickness) smooth structures, homogeneous in the flow direction and produced exceptionally by transverse variations in the wall height (for example, longitudinal ridges of different shapes on a smooth wall) and irregular rough surfaces with multidirectional variations in the surface height (for example, roughness streaks).…”
Section: Secondary Flows Near Rough Surfacesmentioning
confidence: 99%